5th EAI International Conference, INTSYS 2021 Virtual Event, November 24–26, 2021 Proceedings - Ferreira, J.; Martins, A. (2022)
We are delighted to introduce the proceedings of the fifth edition of the International Conference on Intelligent Transport Systems (INTSYS 2021) from the European Alliance for Innovation (EAI). This conference brought together researchers, developers, and practitioners from around the world who are leveraging and developing Intelligent Transportation Systems (ITS) to increase efficiency, safety, and mobility, and tackle Europe’s growing emission and congestion problems. INTSYS 2021 covered the following topics: disruptive technology for intelligent transportation systems; intelligent transportation systems in epidemic areas; data science for cooperative intelligent transportation systems; AI innovation in intelligent transportation systems; diversity in transportation systems for people and goods; public transit planning and operation in the era of automation, electrification, and personalization; edge intelligence for the Internet of Vehicles; blockchain and big data-enabled intelligent vehicular communication; and intent-based networking for 5G-envisioned Internet of Connected Vehicles. This edition received 31 submissions from which the technical program of INTSYS 2021 was developed, consisting of 15 full papers. All papers were subjected to a double-blind peer-review process with a minimum of three reviews per paper. Concerning the committees, it was a great pleasure to work with the excellent organizing team of the EAI, which was essential for the success of the INTSYS 2021 conference. In particular, we would like to express our gratitude to Conference Manager Elena Davydova for all the support she provided in all areas. We would like also to express our gratitude to all the members of the Technical Program Committee, who helped in the peer-review process for the technical papers, and thus ensured a high-quality technical program. We would like to thank the extensive list of external reviewers from several areas of expertise and from numerous countries around the world. A special acknowledgement must be addressed to all the authors for their effort producing such good quality papers and also for the extremely rich and positive feedback shared at the conference. We strongly believe that the INTSYS conference provides a good forum for all researchers, developers, and practitioners to discuss all science and technology aspects that are relevant to ITS. It is becoming a privileged space for knowledge sharing and networking. We also expect that the future INTSYS conferences will be as successful and stimulating as this year’s, as indicated by the contributions presented in this volume. December 2021